Interactions of Xanthan Gum and Carboxymethyl Cellulose on Physical and Sensory of Cloudy Asparagus Juice using Response Surface Methodology - Van Linh, Nguyen Thi; Ngoc Mai, Vuong Thi; Yen Nhi, Tran Thi; Lam, Tri Duc (Asian Journal of Chemistry, 2019)
This study aims to investigate the effect of xanthan gum and carboxymethylcellulose on physical and chemical qualities of green asparagus juice. We adopted the surface-response method and the CCD experiment design with respect to three response variables including stability, viscosity and colour of the product. It was revealed that both xanthan gum and carboxymethylcellulose concentrations are both positively correlated with viscosity and stability of the product. In addition, the coefficient of the interaction of xanthan gum and carboxymethylcellulose was not significant (p < 0.05). In sensory evaluation, both carboxymethylcellulose and xanthan gum were found to be influential on product state. However, hydrocolloid concentration effects were not profound on perceived product colour and odour.